Proses Komunikasi Organisasi Penelitian Mengenai Proses Komunikasi pada Dinas Pendidikan Kabupaten Solok Selatan dengan Permasalahannya dan Pengaruhnya terhadap Pegawai - Pamel Liskardani; Nurhizrah Gistituati; Yahya Yahya (Jurnal Bahana Manajemen Pendidikan, 2020)
AbstractThis study at the Solok Selatan District Education Office using a quantitative approach as a research method. The analysis used is descriptive analysis with a logical empirical approach as evidence in order to justify the researchers' beliefs or vice versa to build an analysis or conclusion. Data were obtained by the researcher as the main instrument through the interview process with key informants, field notes, recording devices and cameras. The research location is the South Solok Regency Education Office, while the research informants in this case varied based on the accuracy of the selection of key informants who mastered the problem with the snowball sampling technique. The results showed the organizational communication process at the South Solok Regency Education Office was understood by various kinds of reasoning, from complex understanding to simple understanding. Organizational communication here appears to have many barriers to its impact on performance